Tunay na repormang agraryo ipaglaban ([Quezon City] AsiaVision Media Foundation in cooperation with Forum for Rural Concerns(FRC), 1988)
Features the three-day Agrarian Reform Express staged by the Kilusang Magbubukid ng Pilipinas (KMP). Affiliate peasant group from Northern Luzon and Southern Luzon traveled hundreds of kilometers to reach Manila
in Filipino